Pickleball : a case study of North America's fastest growing game - Mahoney, Tara Q. (SAGE business cases., 2024)
Pickleball is the fastest growing sport across North America. It has grown at an exponential pace, attracting the attention of recreational participants as well as professional athletes and celebrities such as LeBron James and Mark Cuban. While the sport appeals to older athletes, younger participants represent the fastest growing demographic in the sport. Pickleball has also expanded with the inclusion of three professional leagues featuring top players, large purses, and tournaments around the United States. This case study provides information about the current pickleball landscape and how organizations and investors can capitalize on the popularity of this sport.